Attribution of Sijo Song Authorship to Historical Figures: Sijo of Late Goryeo and Early Joseon - Park, Jaemin (Seoul journal of Korean studies, 2022)
This study examines the authenticity of sijo songs attributed to the late Goryeo (918–1392) and early Joseon (1392–1897) periods. These sijo songs primarily adhere to themes of loyalty to the ruined Goryeo dynasty, or to the tragic execution of King Danjong (r. 1452–1455) in the early Joseon period. The former is typically represented by Jeong Mongju 鄭夢周 and Gil Jae 吉再, and the latter by Wang Bangyeon 王邦衍 and Seong Sammun 成三問. The background stories and attributed authorship of sijo songs are not always aligned with historical facts and often contradict official records. The background stories first emerged in unofficial history books in the seventeenth century, though the original sijo texts predate these narratives. At the time, the sarim 士林 (Neo-Confucian literati without political power) class played a pivotal role in developing these background stories. They yearned to restore the loyalists’ honor and consolidate their ideological and political power; thus, they disseminated sijo songs associated with stories of loyalty through unofficial historical texts. Later, the compilers of public songbooks affirmed the sijo–author relationship in songbooks that proliferated in the eighteenth and nineteenth centuries. Consequently, the myths of early sijo and loyalty were formed and solidified. KCI Citation Count: 0